Modified, optimized method of determination of Tributyltin (TBT) contamination in coastal water, sediment and biota in Sri Lanka - Bandara, K.R.V; Chinthaka, S.D.M; Yasawardene, S.G; Manage, P.M (Elsevier, 2021)
Tributyltin (TBT) is a toxic organotin compound that belongs to the group of Persistent Organic Pollutants (POPs) and it is documented to cause severe sexual disorders development in aquatic fauna. According to the present study, The TBT concentration in coastal water ranged from 303 ± 7.4 ngL􀀀 1 to 25 ± 4.2 ngL􀀀 1 wherein sediment was from 107 ± 4.1 ngKg􀀀 1 to 17 ± 1.4 ngKg􀀀 1. TBT in Perna viridis was found to range from 4 ± 1.2 ngKg􀀀 1 to 42 ± 2.2 ngKg􀀀 1 wet weight and in ascending order of the body weight. The highest TBT level in water and sediment was found in the Colombo port where the highest level of TBT in P. viridis (42 ± 2.2 ngKg􀀀 1) was recorded from the Dikkowita fishery harbor. A positive correlation between the number of male P. viridis and TBT level (p < 0.05) suggests possible reproductive impairment in aquatic animals exposed continuously to a high concentration of TBT.
Keywords: Tributyltin (TBT) Harbors Sediment Perna viridis Imposex